Plant nutrients recovery from aflatoxin B1 contaminated corn through co-composting. Issue 2 (April 2019) - Tacconi, Chiara; Cucina, Mirko; Zadra, Claudia; Gigliotti, Giovanni; Pezzolla, Daniela
Graphical abstract: Highlights: Co-composting was carried out to assess the AFB1 removal and plant nutrients recovery. AFB1 did not influence the co-composting processes. Compost quality was not affected by AFB1. The AFB1 concentration was reduced in the final compost. Co-composting with organic wastes is feasible to recycle contaminated corn. Abstract: Climate change and incorrect agronomic practices in crop management, before and after harvesting, can cause an increase in the annual quantity of aflatoxin B1 (AFB1) contaminated corn production. The aim of this study was to evaluate the suitability of AFB1 contaminated corn for composting, in order to recover plant nutrients and degrade AFB1. Two different mixtures were prepared (mixture PS comprising 12% contaminated corn + 40% pig slurry + 40% wood chips + 8% cereal straw w/w and mixture OFMSW comprising 14% contaminated corn + 43% municipal organic solid waste + 43% wood chips w/w) and treated through static composting using passive aeration. During composting, several parameters were analysed to assess the possible influence of AFB1 on the process. The quality of the final compost was also evaluated and the AFB1 residues were determined through HPLC. The evolution of the composting was not affected by AFB1 and the mycotoxin concentration was strongly reduced at the end of the process (the AFB1 removal was 85.7% and 97.3% in mixture PS and OFMSW, respectively). The final composted material was characterised by high agronomic quality and, thus, composting may represent a suitable strategy to recover plant nutrients from aflatoxin B1 contaminated corn.